Surgical experience and different glove wearing conditions affect tactile sensibility - Man, Tanita; Jiang, Jun; Schulz, Manuela; Kükrek, Haydar; Betzl, Julia; Machens, Hans-Günther; Erne, Holger C.; Moog, Philipp (Heliyon, 2022)
Background - The fingers’ tactile sensibility is essential in surgery, especially in microsurgery. Therefore, surgeons seeking to improve their performance often prefer certain glove brands and wearing habits. There is the need of objectively testing these glove wearing conditions and determine the effect of surgical experience with regard to tactile sensibility by comparing surgeons with non-surgeons. - Methods - This cross-sectional single-center pilot-study was conducted between June and August 2021. Two groups of 27 surgeons and 27 non-surgeons underwent two-point-discrimination (2PD) and Semmes-Weinstein monofilament testing (SWMT) of both index fingers with bare hands and with wearing six different brands of surgical gloves. Different wearing conditions, such as single-gloving, double-gloving, well-fitted, under- and oversized gloves, were evaluated within and between the groups. - Results - Most glove types decreased tactile sensibility (2PD and SWMT) of surgeons and non-surgeons. Interestingly, the thinnest gloves showed similar 2PD values to bare hands in both groups. Double-gloving negatively impacted SWMT, without influencing 2PD. Undersized gloves showed better 2PD and SWMT than well-fitted gloves, while oversized gloves showed no tactile drawbacks. With bare hands and certain glove conditions, the surgeons' 2PD and SWMT was significantly better than the non-surgeons’, indicating a positive effect of surgical experience on tactile sensibility. - Conclusion - Our study demonstrated the positive impact of surgical experience on tactile sensibility, as demonstrated by the surgeons. The sensibility of the gloved hand varies on the surgical glove type, but favors thinner gloves, single gloving (rather than double gloving) and undersized or well-fitted gloves.
Online verfügbar 21 December 2022, Version des Artikels 26 December 2022
Gesehen am 08.05.2024